The effect of proprioceptive neuromuscular facilitation stretching exercises on pain and postural balance in patients with knee osteoarthritis - Dwi Rosella Komala Sari; Raden Andrea Zalfa Zaki Gazella (Physical Therapy Journal of Indonesia, 2023)
Background: Osteoarthritis is a degenerative disease that can cause pain, stiffness, and reduce balance function, thus interfering with daily activities. Proprioceptive Neuromuscular Facilitation Stretching (PNFS) can increase proprioceptive stimulation and activate muscles, reducing pain and improving postural balance in the OA knee. This study aimed to determine the effect of PNFS on reducing pain and increasing postural balance in patients with knee OA. Methods: This type of research was an experimental study with a quick experimental approach without a control group. Nineteen respondents with knee OA were taken by purposive sampling and met the inclusion and exclusion criteria. PNFS was done with the hamstring and quadriceps muscles twice a week for four weeks. The pain was evaluated using a numeric rating scale (NRS), while the dynamic balance was assessed by the timed up and go test (TUG), and static balance was examined by the one-leg stance (OLS) as well as Functional Reach Test (FRT). Results: There was a significant positive effect of PNFS to reduce pain and improve TUG, OLS, and FRT with p-values <0,05, respectively. Conclusion: Pain is the main problem in OA knee and reduced balance. However, PNFS exercises were recommended for rehabilitation management in patients with knee OA.